TINGKAT PENGETAHUAN DAN SIKAP DENGAN TEKNIK MENYUSUI PADA IBU PASCA MELAHIRKAN - Keni, Nia Widia Aprilia; Rompas, Sefti; Gannika, Lenny (Universitas Sam Ratulangi, 2020)
Abstract: Mother's knowledge about breastfeeding techniques will bring a deep understanding of the good or bad impacts of giving breast milk. The method in this study uses a cross sectional research design with the population of all post-partum mothers in the work area of the Wori Health Center in Manado. Sampling is done by non-probability sampling with pruposive sampling technique. The number of samples is 51 respondents. Data is presented in the form of Frequency Tables. Data analysis used is univariate and bivariate analysis using the chi-square analysis method. The results of the study, the majority of respondents have good knowledge and attitude. Respondents who use the wrong breastfeeding technique for respondents who have poor attitudes and knowledge. From the chi-square obtained results from the level of knowledge with breastfeeding techniques with a value of p = 0.00 smaller than Î± = 0.05. Whereas the attitude for breastfeeding technique has a value of p = 0.01 smaller than Î± = 0.05. In conclusion, the results of this study indicate that there is a significant relationship between the level of knowledge and attitudes with breastfeeding techniques in postpartum mothers.Keywords: Knowledge Level, Attitude, and Breastfeeding TechniquesÂ Abstrak: Pengetahuan ibu tentang teknik menyusui akan membawa pemehaman yang mendalam pada dampak baik ataupun buruknya pemberian ASI. Metode ini menggunakan desain penelitian cros sectional dengan populasi seluruh ibu pasca melahirkan di wilaya kerja Puskesmas Wori Manado. Pengambilan sampel dilakukan secara non probability sampling dengan teknik pruposive sampling. Jumlah sampel sebanyak 51 responden. Data disajikan dalam bentuk Frequency Table, Analisis data yang digunakan adalah analisis univariat dan bivariat dengan menggunakan metode analisis chi-square. Hasil penelitian, Mayoritas responden memiliki pengetahuan dan sikap yang baik. Responden yang melakukan teknik menyusui yang salah pada responden yang memiliki sikap dan pengetahuan yang kurang baik. Dari hasil uji chi-square didapatkan hasil dari tingkat pengetahuan dengan teknik menyusui dengan nilai p = 0,00 lebih kecil dari Î± = 0,05. Sedangan untuk sikap dengan teknik menyusui memiliki nilai p= 0,01 ebih kecil dari Î± = 0,05. Kesimpulan, hasil penelitian ini menunjukan ada hubungan yang bermakna antara Tingkat Pengetahuan dan Sikap dengan Teknik Menyusui Pada Ibu Pasca Melahirkan.Kata Kunci: Tingkat Pengetahuan, Sikap, Dan Teknik Menyusui